Facility type and size-stratified analysis of management patterns and outcomes of patients with localized non-functional pancreatic neuroendocrine tumors. Issue 4 (April 2022) - Hue, Jonathan J.; Sugumar, Kavin; Ammori, John B.; Rothermel, Luke D.; Hardacre, Jeffrey M.; Winter, Jordan M.; Ocuin, Lee M.
Abstract: Background: Non-functional neuroendocrine tumors of the pancreas (NF-pNETs) are uncommon. Consensus guidelines have conflicting recommendations. We performed a nationwide analysis of patterns in management and outcomes based on facility type and tumor size. Methods: The National Cancer Database (2004–2016) was queried for patients with localized NF-pNETs (<1 cm, 1–2 cm, >2 cm) stratified by facility type. Management decisions, operative outcomes, and survival were compared. Results: A total of 7170 patients were included in the analysis (<1 cm = 916; 1–2 cm = 2180; >2 cm = 4074). Most patients were treated at academic facilities (62.8%). Over 67% of patients with tumors <1 cm underwent resection, independent of facility type (p = 0.443). There was no association between facility type and operative vs non-operative management of patients with NF-pNETs 1–2 cm in size. Patients treated at academic facilities were more likely to undergo resection for tumors >2 cm compared to other facility types. Resection was associated with improved survival among patients with tumors 1–2 cm (HR = 0.43, p < 0.001) and >2 cm (HR = 0.32, p < 0.001), but not <1 cm (HR = 0.64, p = 0.054), as compared to non-operative management. Conclusion: There is heterogeneity in management of NF-pNETs across facility types. Treatment at academic facilities appears to be associated with higher resection rates for tumors >2 cm. There appears to be an independent association between operative management and improved survival for tumors ≥1 cm in size.